2006
DOI: 10.1016/j.jmb.2006.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ion Exchange in Crystalline Gelsolin

Abstract: Gelsolin is a calcium and pH-sensitive modulator of actin filament length. Here, we use X-ray crystallography to examine the extraction and exchange of calcium ions from their binding sites in different crystalline forms of the activated N and C-terminal halves of gelsolin, G1-G3 and G4-G6, respectively. We demonstrate that the combination of calcium and low pH activating conditions do not induce conformational changes in G4-G6 beyond those elicited by calcium alone. EGTA is able to remove calcium ions bound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…These dynamic light scattering studies concluded that, in solution, the compact Ca 2ϩ -free gelsolin molecule opens upon binding Ca 2ϩ following a sigmoidal relationship, which is reversible and in which 50% "activation" occurs with 30 nM Ca 2ϩ , whereas a maximum R h is reached at ϳ1 M Ca 2ϩ (18). This observed reversibility is also supported by recent EGTA chelation studies on different crystalline forms of the Ca 2ϩ -activated N-and C-terminal halves of gelsolin whereby the subdomains rearranged toward the compact inactive form (20).…”
supporting
confidence: 54%
“…These dynamic light scattering studies concluded that, in solution, the compact Ca 2ϩ -free gelsolin molecule opens upon binding Ca 2ϩ following a sigmoidal relationship, which is reversible and in which 50% "activation" occurs with 30 nM Ca 2ϩ , whereas a maximum R h is reached at ϳ1 M Ca 2ϩ (18). This observed reversibility is also supported by recent EGTA chelation studies on different crystalline forms of the Ca 2ϩ -activated N-and C-terminal halves of gelsolin whereby the subdomains rearranged toward the compact inactive form (20).…”
supporting
confidence: 54%
“…Sequences were oriented and colored using Swiss-PdbViewer (DeepView), v4.0 (http://spdbv.vital-it.ch/). Supervillin amino acids 1326–1699 were automatically aligned with gelsolin repeats 4 through 6 (G4–G6, amino acids 445–765; PDB: 2FH1B) (Chumnarnsilpa et al 2006). Additional structural elements in supervillin residues 1019–1306 were aligned with gelsolin repeats 2 and 3 (G2–G3) and the G3–G4 linker (gelsolin amino acids 189–444; PDB: 2FGHA) (Urosev et al 2006) in forced comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, then, the crystal structure of equine G1-G3 in a complex with actin (9) shows the type 2 site in G2 to be incompletely formed and devoid of Ca 2ϩ . That this locale within G2 can be induced to form a valid metal ion-binding site is verified by the ability of Tb 3ϩ ions to soak into crystals of the complex of equine G1-G3 with actin and occupy the site (8). Furthermore, a Cd 2ϩ is found in the structure of isolated human G2, coordinated by the side chains of Asp-187, Glu-209, and Asp-259 (10).…”
mentioning
confidence: 88%
“…Sequence and structural data (7)(8)(9)(10) suggest that activated actin-bound gelsolin has eight Ca-binding sites. Two, associated with G1 and G4, are identified as type 1, with the metal ion coordinated by residues from both actin and gelsolin (7).…”
mentioning
confidence: 99%